SPEAKING BODIES, VISIBLE VOICES: NARRATIVE TENSION IN COPPOLA’S APOCALYPSE NOW: REDUX (2001) - Mori, Alifa Syauqina; Priyatna, Aquarini; Adipurwawidjana, Ari J (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
Francis Ford Coppola’s Apocalypse Now: Redux (2001), a 2001 re-release of his 1979 Vietnam War epic, sparked significant discussions among both academic scholars and mainstream media. The extended version, which features almost an hour-long addition of new scenes, challenged the question of the film’s continued relevance within the evolving Hollywood industry. While the original version may have highlighted the horror and dehumanization of the Vietnam War, it was also criticized for depicting women as one-dimensional sexual objects and effectively silencing their voices. However, by utilizing Verstraten’s notion of filmic narrative, Mulvey’s visual pleasure, and Stark’s narrative voicelessness, this research aims to show how narrative tension is displayed in Apocalypse Now: Redux and how it highlights the representation of the female characters’ subjectivity. We argue that the Redux version offers a notable difference from the stereotypical portrayal of women in war film. By incorporating the newly added scenes, Apocalypse Now: Redux provides the female characters with more agency and individuality, allowing them to move beyond the limitation of being mere decorations.